Fructans Prime ROS Dynamics and Botrytis cinerea Resistance in Arabidopsis - TOKSOY ÖNER, EBRU (MDPI, 2020)
Naturally derived molecules can be used as priming or defense stimulatory agents to protect against biotic stress. Fructans have gained strong interest due to their ability to induce resistance in a number of crop species. In this study, we set out to establish the role of fructan-induced immunity against the fungal pathogen Botrytis cinerea in Arabidopsis thaliana. We show that both inulin- and levan-type fructans from different sources can enhance Arabidopsis resistance against B. cinerea. We found that inulin from chicory roots and levan oligosaccharides from the exopolysaccharide-producing bacterium Halomonas smyrnensis primed the NADPH-oxidase-mediated reactive oxygen species (ROS) burst in response to the elicitors flg22, derived from the bacterial flagellum, and oligogalacturonides (OGs), derived from the host cell wall. Neither induced a direct ROS burst typical of elicitors. We also found a primed response after infection with B. cinerea for H2O2 accumulation and the activities of ascorbate peroxidase and catalase. Sucrose accumulated as a consequence of fructan priming, and glucose and sucrose levels increased in fructan-treated plants after infection with B. cinerea. This study shows that levan-type fructans, specifically from bacterial origin, can prime plant defenses and that both inulin and levan oligosaccharide-mediated priming is associated with changes in ROS dynamics and sugar metabolism. Establishing fructan-induced immunity in Arabidopsis is an important step to further study the underlying mechanisms since a broad range of biological resources are available for Arabidopsis.
Keywords: fructan; Botrytis cinerea; Arabidopsis thaliana; priming; reactive oxygen species; sweet immunity; sugars; BETA-AMINOBUTYRIC ACID; PLANT DEFENSE RESPONSES; NADPH OXIDASE RBOHD; OXIDATIVE BURST; INFECTION; STRESS; LEAVES; TOMATO; SUGARS; IMMUNITY